2019
DOI: 10.1515/phys-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Ion charge separation with new generation of nuclear emulsion films

Abstract: In hadron therapy, the accelerated ions, interacting with the body of the patient, cause the fragmentation of both projectile and target nuclei. The fragments interact with the human tissues depositing energy both in the entrance channel and in the volume surrounding the tumor. The knowledge of the fragments features is crucial to determine the energy amount deposited in the human body, and - hence - the damage to the organs and to the tissues around the tumor target. The FOOT (FragmentatiOn Of Target) experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Tests carried out at LNS of the FOOT emulsion chambers have already proved their capability in achieving the required FOOT performances in charge separation [37]. Measurements with the full emulsion chamber setup have been already performed at GSI in 2019 and 2020 using 16 O beams of 200 and 400 MeV/nucleon kinetic energy and a 12 C beam of 700 MeV/nucleon kinetic energy impinging on C and C 2 H 4 thin targets.…”
Section: The Foot Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests carried out at LNS of the FOOT emulsion chambers have already proved their capability in achieving the required FOOT performances in charge separation [37]. Measurements with the full emulsion chamber setup have been already performed at GSI in 2019 and 2020 using 16 O beams of 200 and 400 MeV/nucleon kinetic energy and a 12 C beam of 700 MeV/nucleon kinetic energy impinging on C and C 2 H 4 thin targets.…”
Section: The Foot Experimentsmentioning
confidence: 99%
“…The use of emulsions is coupled to the continuous development in the field of automated scanning system techniques: last generation microscopes [61][62][63][64] allow very fast scanning with wide angular acceptances of huge data sets. Furthermore, it was demonstrated that a controlled fading of the emulsions in terms of different thermal treatments extends their dynamical range when crossed by different ions, providing charge identification capabilities [37,65,66]. The possibility to measure particles emitted with an angular acceptance above 70°w ith respect to the incident angle, coupled to the very high spatial resolution and charge identification capability, made the nuclear emulsion technology an ideal choice for new generation of measurements of differential fragmentation cross sections.…”
Section: The Emulsion Spectrometermentioning
confidence: 99%
See 1 more Smart Citation
“…For the emulsion setup, the performances show a very good efficiency (> 99%) in charge separation; more details have been published in Ref. 4.…”
Section: Electronic Setupmentioning
confidence: 99%
“…The production cross sections of the target fragments are a topic of great interest but poor data are available: the direct measurement of target fragments is extremely difficult due to the short range of produced secondaries that have low probability to escape the target. The FOOT (FragmentatiOn Of Target) experiment [7][8][9][10] plans to use a complex experimental setup and an inverse kinematic approach to investigate the target fragments.…”
Section: Introductionmentioning
confidence: 99%